Effect of Blended Instructional Strategy on Colleges of Education Students’ Achievement, and Retention in Electronics Technology in North-East Nigeria - Zechariah, Ishaku; Chinda, Patrick Duhu (Darul Yasin Al Sys, 2024)
This study examined the Effect of Blended Instructional Strategy on Colleges of Education Students’ Achievement, and Retention in Electronics Technology in North-East Nigeria. College of Education is one of the tertiary institutions in Nigerian alongside other institutions like polytechnics, monotechnics etc. However, Colleges of Education are the institutions that are exclusively saddled with the responsibility of training teachers who will in turn teach at the Junior Secondary School level of education in Nigeria. They are expected to realize the objectives of NCE (T) .This implies that the graduates should invariably be technologist as well as agents of technological advancement both in the classroom and in the society. Three research questions and eight hypotheses were formulated to guide the study. The study adopted Quasi -experimental design involving pre-test post-test control group. The population of the study was 73 Electronics Technology students in six Colleges of Education North-East Nigeria. The sample was 36 Electronics Technology students in three Colleges of Education. Digital Electronics Achievement Test (DEAT), Digital Electronics Retention Test (DERT) were developed by the researcher as the instruments for data collection. The validated DEAT and DERT were tested for internal consistency using Pearson Product Moment Correlation. The reliability coefficients of the instruments were found to be 0.915 and 0.895 respectively. Data were collected and analysed using SPSS the research questions were answered using mean, standard deviation while t-test, ANCOVA, ANOVA and Scheffe’s statistical tools were used to test the null hypotheses at 0.05 level of significance. The results showed that there was significant difference in achievement test scores between BIS and TIS strategy in favour BIS. More so, the results show significant differences in students’ achievement retention in favour of BIS. Study also revealed that there was no significant difference in achievement test scores of male and female students when taught Digital Electronics using BIS as well as retention. The study concluded that and BIS enhanced the academic achievement, and retention in Digital Electronics Technology Students,. It was Recommended that BIS should be encourage in Colleges of Education Electronics Lesson Delivery.